Delineation of groundwater recharge zones in lateritic terrains using geospatial techniques - A. Ajayakumar; Rajesh Reghunath (Discover Geoscience)
Abstract This study attempts to narrow down the groundwater potential zones in a river basin where laterites form the major aquifer rock. The study is attempted in the Ithikkara River Basin (IRB), located in the southern Western Ghats of Kerala, India. Groundwater scarcity is a pressing issue in this region, warranting effective management of the groundwater resources. To address this important problem, satellite data (Landsat 8 OLI, SRTM DEM) and geospatial techniques were employed to assess the hydrogeological potential. Various thematic maps such as geology, geomorphology, drainage density, lineament density, slope, land use, relative relief and mean depth to water table were integrated in the spatial platform to derive suitable sites for artificial recharging. The thematic layers were subjected to weighted overlay analysis using QGIS and SAGA GIS to delineate groundwater potential area. The resultant map has been validated with well yield data obtained from the Central Ground water Board, Government of India and field data. It is found that the lower reaches along the western portions of the basin is more suitable for artificial recharging of aquifers, owing to the presence of sedimentary rocks and valley fills.